2022
DOI: 10.1002/capr.12611
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the therapists' experiences of working with community reinforcement and family training

Abstract: Community reinforcement and family training (CRAFT) was developed to help and support concerned significant others (CSO) of people with, for example, alcohol use disorder. The aim of this study was to investigate therapists' experiences of working with CRAFT and their experiences of the CSOs receiving CRAFT. The study has a qualitative design and is based on three focus group interviews with 17 therapists. Interviews were analysed using thematic analysis. The analysis revealed six themes and four subthemes: Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a prior, qualitative study of the experiences of the therapists, who performed the intervention in the Danish CRAFT study, the therapist considered that CRAFT worked better, if the CSO had told the IP that they participated in CRAFT. Based on what the CSOs reported on homework assignments etc., the therapists found that when the CSOs had informed the IP, it allowed the CSO and IP to have a more open discussion about the CRAFT program and other issues related to the alcohol problem (31).…”
mentioning
confidence: 99%
“…In a prior, qualitative study of the experiences of the therapists, who performed the intervention in the Danish CRAFT study, the therapist considered that CRAFT worked better, if the CSO had told the IP that they participated in CRAFT. Based on what the CSOs reported on homework assignments etc., the therapists found that when the CSOs had informed the IP, it allowed the CSO and IP to have a more open discussion about the CRAFT program and other issues related to the alcohol problem (31).…”
mentioning
confidence: 99%